The Question of 'Cultural Language' and Interdialectal Norm in 16th Century Slovakia A Phonological Analysis of 16th Century Slovak Administrative-Legal Texts - Lauersdorf, Mark Richard (Slavistische Beitraege, 1996)
In the series Slavonic Contributions Slavic dissertations of German-speaking countries as well as occasionally also American, English and Russian are published. In addition, the series provides a forum for anthologies and monographs of established scientists.